Ethanol Inhibition of Thrombus Formation on Collagen-Coated Glass - Owens, Charlene K; Mclntire, Larry V; Lasslo, Andrew (Thrombosis and Haemostasis, 1990)
Epi-fluorescent video microscopy was used to evaluate the effect of ethanol on platelet mural thrombus formation. Whole blood, treated with ethanol, was perfused over collagen coated glass in a parallel-plate flow chamber at a shear rate of 1,000/s. Digital image processing and photodiode measurements were used to analyze the dynamics of thrombus growth on this surface. Ethanol concentrations as low as 0.02% v/v were found to inhibit 45 + 33% (± S.D.) of normal platelet accumulation on the slide while 0.2% v/v ethanol effected an 82 ± 15% inhibition of mural thrombus formation. While platelet adhesion to the collagen surface appeared unaffected by ethanol concentrations up to 0.1% v/v, 0.2% v/v ethanol had an effect on adhesion as well as aggregation. These results imply that low ethanol concentrations inhibit the formation of mural thrombi in a model of a damaged blood vessel at physiological shear rates. This inhibition would not be detected in systems which measure bulk aggregation, e.g. in aggregometric determinations.